2018
DOI: 10.1021/acs.jpcc.8b08488
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of 2,7-Dipyridylfluorene Derivatives in Single-Molecule Junctions

Abstract: A series of 2,7-dipyridylfluorene derivatives have been synthesized with different substituents (2H, 2Me, 2OMe, 2CF3, and O) at the C(9) position. Experimental measurements on gold|single-molecule|gold junctions, using a modified scanning tunneling microscope-break-junction technique, show that the C(9) substituent has little effect on the conductance, although there is a more significant influence on the thermopower, with the Seebeck coefficient varying by a factor of 1.65 within the series. The combined expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
(56 reference statements)
1
29
0
Order By: Relevance
“…To address the problem of increasing the thermoelectric performance of organic molecules, Finch et al 10 demonstrated theoretically that large values of the Seebeck coefficient could be obtained by creating transport resonances and anti-resonances within the HOMO-LUMO gap and tuning their energetic location relative to the Fermi energy. Following these pioneering works, several experimental [11][12][13][14][15][16][17][18][19][20] and theoretical studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34] have attempted to probe and improve the thermoelectric performance of single molecules. However, progress has been hampered by the additional complexity of thermoelectric measurement set-ups, because unlike measurements of single-molecule conductance, Seebeck measurements require additional control and determination of temperature gradients at a molecular scale.…”
Section: Introductionmentioning
confidence: 99%
“…To address the problem of increasing the thermoelectric performance of organic molecules, Finch et al 10 demonstrated theoretically that large values of the Seebeck coefficient could be obtained by creating transport resonances and anti-resonances within the HOMO-LUMO gap and tuning their energetic location relative to the Fermi energy. Following these pioneering works, several experimental [11][12][13][14][15][16][17][18][19][20] and theoretical studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34] have attempted to probe and improve the thermoelectric performance of single molecules. However, progress has been hampered by the additional complexity of thermoelectric measurement set-ups, because unlike measurements of single-molecule conductance, Seebeck measurements require additional control and determination of temperature gradients at a molecular scale.…”
Section: Introductionmentioning
confidence: 99%
“…S80 † the results are presented in order of increasing meta-connected conductance, with X = SO 2 giving the with the values of the para-connected systems (blue stars). 22 The error bars of G are the standard deviation obtained from Gaussian fits applied to the conductance peaks observed in the corresponding 1D histogram. The error bars of S are the relative error of the thermopower obtained from the linear regression fitted to the corresponding V th vs. ΔT data.…”
Section: Quantum Transport Measurementsmentioning
confidence: 99%
“…Here we investigate the sensitivity of QI to the bridging atom X connecting the two phenyl rings (Fig. 1) in a series of bridged biphenyl-based molecules and in particular, how QI is affected by their meta (molecules 1-7) versus para (molecules 8-10) 22 connectivity to terminal pyridyl rings, which link to the external electrodes. Molecules 1-7 were chosen based on synthetic accessibility and to provide a wide range of electronic properties by introducing heteroatom substitution at the bridging position (2, 4, 5 and 7).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Single-molecule electronic junctions 5-12 and self-assembled monolayers [13][14][15] have been investigated intensively over the past few years, because their room-temperature electrical conductance has been shown to be controlled by destructive quantum interference (DQI). [16][17][18][19][20] More recently the effect of quantum interference on the Seebeck coefficient of single molecules has also been studied [21][22][23][24][25][26] . Figure 1 (A) illustrates an example of a room-temperature constructive quantum interference (CQI) effect, in which electrical current is injected into and collected from an anthracene molecular core, via the green arrows, or alternatively via the red arrows.…”
mentioning
confidence: 99%